Development and Testing of an Interpretational Bias Measure of Dental Anxiety - Heaton, Lisa J.; Leroux, Brian G.; Ramsay, Douglas S. (Frontiers in Dental Medicine, 2022)
Objectives We hypothesized that individuals with dental care-related anxiety and fear would interpret ambiguous dental situations more negatively than non-anxious individuals. The objectives of these studies were to develop and test a Measure of Dental Anxiety Interpretational Bias (MoDAIB). Methods In the development phase, participants completing an online survey provided qualitative and quantitative assessments of dental scenarios that could be interpreted in either positive or negative ways. Scenarios producing the greatest difference in visual analog (VAS) scores between individuals with high vs. low dental anxiety as measured by the Modified Dental Anxiety Scale (MDAS) were included in the MoDAIB. In the testing phase, participants completed an online survey including the newly developed MoDAIB and dental anxiety measures. Results In the development phase, participants (N = 355; 65.6% female) high in dental anxiety (MDAS ≥ 19) gave significantly higher (i.e., more negative) VAS scores to all the dental scenarios than did those low in dental anxiety (p's < 0.05). In the testing phase, the MoDAIB was significantly and positively correlated with the MDAS (r = 0.68, p < 0.001), meaning that those who were high in dental anxiety selected negative interpretations of ambiguous dental scenarios significantly more often than did individuals low in dental anxiety (p's < 0.05). The MoDAIB showed good content validity and test-retest reliability. Conclusions Individuals high in dental anxiety interpret ambiguous dental situations more negatively than do less anxious individuals. Understanding individuals' interpretational styles may help dental providers avoid miscommunications. Interventions that train dentally anxious patients to consider more positive interpretations may reduce dental anxiety and should be investigated.